On the internal structure of the current sheet in the pulsar wind. Issue 2 (2nd November 2017) - Prokofev, V. V.; Arzamasskiy, L. I.; Beskin, V. S.
Abstract: We investigate the internal structure of the current sheet in the pulsar wind within force-free and two-fluid MHD approximations. Within the force-free approximation we obtain general asymptotic solution of the Grad–Shafranov equation for quasi-spherical pulsar wind up to the second order in small parameter ε = (Ω r / c ) −1 . The solution allows an arbitrary latitudinal structure of the radial magnetic field, including that obtained in the numerical simulations of oblique rotators. It is also shown that the shape of the current sheet does not depend on the latitudinal structure. For the internal region of the current sheet outside the fast magnetosonic surface where the force-free approximation is not valid we use two-fluid MHD approximation. Carrying out calculations in the comoving reference frame, we succeed in determining intrinsic electric and magnetic fields of a sheet. It allows us to analyse time-dependent effects which were not investigated up to now. In particular, we estimate the efficiency of the particle acceleration inside the sheet. Finally, after investigating the motion of individual particles in the time-dependent current sheet, we find the width of the sheet and its time evolution self-consistent.